Chemotherapy-induced Spontaneous Pneumothorax: Case Series - Een Hendarsih; Trinugroho H Fadjari; Amaylia Oehadian (Acta Medica Indonesiana, 2016)
We present 2 patients who developed spontaneous pneumothorax (SP) following rapid regression of lymphoma and rhabdomyosarcoma with lung metastases. Case 1, a 43-year old man was admitted to our hospital with dyspnea 10 days before admission. He denied any recent trauma or previous treatment for lung tuberculosis. Three weeks prior to admission, he received first cycle of CHOP for non-Hodgkin’s lymphoma stage II BE. Chest X-ray consistent with right pneumothorax. After treatment with chest tube drainage for about 1 month, the patient recovered and chemotherapy could be continued without further complications. Case 2, a 35- year old man was admitted to other hospital with dyspnea and chest pain on day 4 after second cycle of systemic combined chemotherapy for rhabdomyosarcoma stage IV (lung metastases) with doxorubicin, ifosfamide, mesna, and dacarbazine. Chest X-ray showed hydropneumothorax on right and left lung. After treatment with chest tube drainage about 2 weeks, the patient recovered and chemotherapy could be continued without further complications. The mechanism of pneumothorax following chemotherapy is not clearly understood yet, however, several hypotheses have been considered: 1) the rupture of a subpleural bulla after chemotherapy; 2) the rupture of an emphysematous bulla in an over expanded portion of the lung which is partially obstructed by a neoplasm; 3) tumor lyses or necrosis due to cytotoxic chemotherapy directly induces the formation of fistula. Dyspnea and chest pain suddenly appear during successful chemotherapy for metastatic chemosensitive tumors should alert the physician to the possibility of SP. The treatment is directed toward lung re-expansion. Chemotherapy induced pneumothorax should be considered as oncologic emergency.